Realistic analysis and design of partially prestressed concrete beams using a non-linear approach - 242811 Ahmed El-Tayeb Ahmed El-Hassan (Skudai : Universiti Teknologi Malaysia, 2002)
Thesis (Doctor of Philosophy) - Universiti Teknologi Malaysia, 2002